Analisis Persepsi Kemanfaatan Penggunaan Google Classroom Pada Pembelajaran Akuntansi - Ni Luh Putu Anom Pancawati (Cetta: Jurnal Ilmu Pendidikan, 2021)
The COVID-19 pandemic in almost all countries in the world has caused restrictions on human interaction. As one solution to reduce the spread of COVID-19, learning that was previously carried out offline has switched to utilizing e-learning, this is one of the methods used as a medium to reduce the risk of being infected with COVID-19. This study aims to determine the perceived benefits of using google classroom for students in accounting learning. This research was conducted at the Gde Pudja Mataram State College of Hinduism, majoring in Hindu Economics for students who taking Accounting courses. Data collection was carried out by providing a questionnaire consisting of several questions and described using the Unified Theory of Acceptance and Use of Technology (UTAUT) construction. Based on the results of the analysis, this study found that the variable performance expectancy, social factors, and use behavior had a fairly good acceptance. On the other hand, the results of the effort (effort expectancy) show significant results, especially regarding the ease of student acceptance of accounting learning. Based on the research results, it can be concluded that students find it difficult to understand and apply accounting practices using google classroom learning media.